Changes in Biomarkers of Cigarette Smoke Exposure After 6 Days of Switching Exclusively or Partially to Use of the JUUL System with Two Nicotine Concentrations: A Randomized Controlled Confinement Study in Adult Smokers. Issue 12 (23rd June 2021) - Cohen, Gal; Goldenson, Nicholas I; Bailey, Patrick C; Chan, Stephanie; Shiffman, Saul
Abstract: Introduction: Evidence suggests that cigarette smokers who switch to electronic nicotine delivery systems (ENDS) reduce their exposure to harmful toxicants and carcinogens. It is unclear if dual-use is associated with decreases in exposure to toxicants. Methods: This parallel-group confinement study assessed changes in biomarkers of exposure (BOEs) over six days among healthy adult smokers who were randomized into 1 of 11 study groups: eight JUUL-brand System (JUUL) groups (4 JUUL flavors [Virginia Tobacco, Menthol, Mint, Mango] × 2 nicotine concentrations [5.0% or 3.0% by weight]); Dual-Use group used preferred JUUL flavor (5.0% nicotine) and ≤50% usual brand (UB) cigarettes/day; UB Cigarette group and one group abstained from all tobacco/nicotine product use (Abstinence group). Urine and blood analysis assessed changes in primary BOE endpoints (NNAL, 3-HPMA, MHBMA, S-PMA COHb) and secondary BOE endpoints (NNN, HMPMA, CEMA, 1-OHP, O-toluidine, 2-NA, 4-ABP) among 279 adult smokers. Results: In JUUL groups, median percent reductions in primary BOEs (Day 6–Baseline) were 90%–≥100% of Abstinence; there were no significant differences between JUUL groups and Abstinence. All reductions in JUUL groups were substantially and statistically significantly greater than reductions in the UB Cigarette group ( p s < 0.025). Median reductions in primary BOEs in the Dual-Use group were 43%–55% of Abstinence. Similar results were observed for secondary BOEs. Conclusion: This study suggests that the use of JUUL as a complete or partial substitute (i.e., dual-use with ≥50% reduction in cigarette consumption) for combustible cigarettes can substantially reduce exposure to multiple toxins associated with cigarette smoking. Implications: This study adds to the growing body of evidence supporting the utility of ENDS products as potentially reduced-harm alternatives to cigarettes for adult smokers. Adult smokers who switched completely from cigarette smoking to use of the JUUL System ("JUUL") in two nicotine concentrations (5.0% and 3.0%) and four flavors significantly reduced their exposure to multiple classes of cigarette-related toxicants. Additionally, smokers who used JUUL and continued smoking but reduced their daily cigarette consumption by ≥50% (dual users) also significantly reduced their toxicant exposure compared to cigarette smoking.